Metode Pendidikan Akhlakul Karimah Anak Menurut Imam Al-Ghazali - Husnul Qodim (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This text is intended to restate the importance of the methods of education toward children. The methods of education which have been felt have been in crisis of morality or civility have become important concern in the writing. By readopting child- rearing methods according to imam al-ghazali for a knowledge of sexually based educational methods that emphasize the importance of moral education and character without putting academic education at the heart of a typical islamic education. Given the importance of al-ghazali's thinking in the islamic world research this time using literature research methods to understand al-ghazali's thinking in education. According to research, the method of child education, according to al-ghazali, emphasizes the implanting of virtue and the cultivating of virtue, which rests on each child's soul, which could be accomplished if the educator or parent could be a good teacher to the student. In addition to sharpening a child's intelligence in the learning process of al-ghazali, using the method of dialogue used in the learning process was intended to strengthen memory and deepen a child's understanding of a topic or problem that he was learning. Exemplary methods and dialogue work to develop the cognitive, affective, and psychosomatic aspects that are present in humans.